Filipin as a Tool for the Study of Blood Coagulation Reactions - van der Plas, P. M; Kraan, L; Hemker, H. C (Thrombosis and Haemostasis, 1972)
The influence of polyene suspensions on blood coagulation was investigated. The following conclusions can be drawn :1. Polyenes in suspension inhibit coagulation, the sequence of activity is in accordance with the lytic activity on micro - organisms and lipid mono- and bilayers.2. Alteration of the molecule by means of hydrogenation of the conjugated system or irradiation in the presence of FMN diminish the lytic activity and inhibition of coagulation in the same sense.3. The composition and amount of lipid are important for the magnitude of the inhibition.4. The inhibition can be decreased by pre-incubation of the polyene with cholesterol. This can be explained by the formation of polyene-cholesterol complexes.5. Polyenes do not inhibit the thrombin-fibrinogen-interaction in plasma.